Systematic Chromatin Accessibility Analysis Based on Different Immunological Subtypes of Clear Cell Renal Cell Carcinoma - Zhang, Shiqiang; Zheng, Wenzhong; Jiang, Donggen; Xiong, Haiyun; Liao, Guolong; Yang, Xiangwei; Ma, He; Li, Jun; Qiu, Miaojuan; Li, Binbin; Sun, Chunhui; Zhao, Jing; et al. (Frontiers in Oncology, 2021)
Background Recent research of clear cell renal cell carcinoma (ccRCC) is focused on the tumor immune microenvironment (TIME). Chromatin accessibility is critical for regulation of gene expression. However, its role in different immunological subtypes of ccRCC based on immune cell infiltration has not been systematically studied. Methods Five hundred thirty patient data from The Cancer Genome Atlas Kidney Renal Clear Cell Carcinoma (TCGA-KIRC) were adopted to estimate immune cell infiltration. Twenty-four types of immune cells were evaluated with single-sample Gene Set Enrichment Analysis (ssGSEA). Patients were divided into two clusters based on immune cell infiltration. Systematic chromatin accessibility analysis was conducted based on the two clusters. Results We compared the relative expression of the immune gene signatures among 530 patients of TCGA-KIRC using ssGSEA. Overall survival (OS) analysis revealed 10 types of immune cells were significantly associated with prognosis. Patients were divided into two clusters based on 24 types of immune cell infiltration. Immune cell signals as well as PD-1/PD-L1 signal were higher in cluster 1. Among the two clusters, 2,400 differential peaks were found in TCGA-KIRC Transposase Accessible Chromatin with high-throughput sequencing (ATAC-seq) data. The distribution of differential peaks and prognosis-related immune cells in 23 chromosomes are essentially the same. There is no peak distribution downstream. The proportion of peaks upstream of the 5’ transcription start site decreases, and both sides of binding regions of the TSS 0.1-1 kb becomes smaller. Enrichment analysis of GO and KEGG of these differential peaks showed that they are remarkably related to the immune regulation in tumor microenvironment. Known motifs and de novo motifs were found by linking motif annotations to different peaks. Survival analysis of related motif transcription factors were prognostic. The GSEA enrichment analysis showed that high SP1 expression positively correlates with TGF-beta signaling and inflammatory response, while negatively correlates with TNF-alpha signaling via NFKB. High KLF12 expression negatively correlates with interferon gamma response, IL2-STAT5 signaling, TNF-alpha signaling via NFKB, IL6-JAK-STAT3 signaling. Conclusion The abnormality of chromatin accessibility may play an important regulatory role in ccRCC immunity.